Leksikon dan nilai kultur Suwawa Gorontalo dalam ritual Momeqati - Lihawa, Kartin (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This research aims to examine the use of the Suwawa lexicon, particularly related to traditional objects in the momeqati ritual and its associated socio-cultural values. The research employs a descriptive qualitative method using observation, interviews, and note-taking techniques to collect the data. The results show that the lexicon related to traditional elements of the momeqati ceremony is dominated by aesthetic values, including beauty, fragrance, harmony, health, perfection, softness, coolness, happiness, welfare, cleanliness, purity, glory, and enjoyment. Based on the Suwawa–Gorontalo community’s conceptual framework, the momeqati ritual ceremony is associated with girls’ jobs, which are intended to educate young women on household management and personal refinement in order to attract others. In conclusion, there are 46 lexical units related to traditional elements in the momeqati ritual, consisting of 35 aesthetic values, 28 ethical values, 16 religious values, 15 social values, and 6 cultural and educational values.